The Effectiveness of Journalist Questions Technique on Teaching Writing - Pratiwi, Aisyah; Wahyuni, Zeli; Indrawati, Indrawati (EEdJ: English Education Journal, 2022)
The aim of this study was to find out the significant difference of the skill in writing of recount text between the students who were taught by using Journalist Questions Technique and those who were not. In this study, the researcher used quantitative approach with quasi experimental design which was conducted at SMP Negeri 1 Pangkalpinang in academic year 2021/2022. The researcher used purposive sampling technique and two classes were taken as samples, while the samples of this study were 77 students. The result of the test was analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. The finding showed that the students who taught by using Journalist Questions Technique got higher score than those who taught by non using Journalist Questions Technique. It could be seen from the result of the mean score of post-test in the experimental group was higher (85.68) than the mean score in the control group (80.00). Furthermore, the result of independent sample t-test stated that t-obtained (3.605) was higher than critical value of t-table (2.00) and the p-output or the significant (2-tailed) was 0.001, lower than computation with significant level 0.05. Thus, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. Therefore, there was a significant difference between who were taught by using Journalist Question Technique and the students who were not.. In conclusion, Journalist Questions Technique has a moderate effect in improving students’ writing ability.